2014
DOI: 10.1038/ncomms4598
|View full text |Cite
|
Sign up to set email alerts
|

The RNA helicase FRH is an ATP-dependent regulator of CK1a in the circadian clock of Neurospora crassa

Abstract: The Neurospora clock protein FRQ forms a complex with casein kinase 1a (CK1a) and FRH, a DEAD box-containing RNA helicase with a clock-independent essential function in RNA metabolism. In the course of a circadian period, FRQ is progressively hyperphosphorylated and eventually degraded. Timed hyperphosphorylation of FRQ is crucial for timekeeping of the clock. Here we show that the ATPase activity of FRH attenuates the kinetics of CK1a-mediated hyperphosphorylation of FRQ. Hyperphosphorylation of FRQ is strict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 44 publications
2
62
0
Order By: Relevance
“…Phosphorylated WCC leaves the frq promoter. As FRQ becomes hyperphosphorylated, it loses its ability to interact with CK1 (39) and WCC (17), becoming therefore a weak repressor of WCC (40). In addition, dephosphorylation of WCC, as well as new synthesis of these proteins, provide active WC-1 and WC-2 to reinitiate the cycle.…”
Section: Figmentioning
confidence: 99%
“…Phosphorylated WCC leaves the frq promoter. As FRQ becomes hyperphosphorylated, it loses its ability to interact with CK1 (39) and WCC (17), becoming therefore a weak repressor of WCC (40). In addition, dephosphorylation of WCC, as well as new synthesis of these proteins, provide active WC-1 and WC-2 to reinitiate the cycle.…”
Section: Figmentioning
confidence: 99%
“…As this theme of dual non-overlapping roles for FRH was emerging, contrasting work based in in-vitro studies asserted that FRH played a more active role in the clock, via its ATPase activity, by stimulating a structural change in FRQ [31]. However subsequent analyses have shown that this ATPase-dependent structural change seems to be specific to the in vitro yeast system used for the experiments and does not occur in Neurospora (personal communication from M. Brunner).…”
Section: New Developments In the Negative Arm Functionmentioning
confidence: 99%
“…Genome Research 1353 www.genome.org RNA helicases (Sun et al 2011;Cruciat et al 2013;Lauinger et al 2014;Alessi et al 2015).…”
Section: Ddx54 In Genotoxic Stress Responsementioning
confidence: 99%